2023
DOI: 10.1002/14651858.cd013308.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Different doses, durations and modes of delivery of nicotine replacement therapy for smoking cessation

Abstract: Background Nicotine replacement therapy (NRT) aims to replace nicotine from cigarettes. This helps to reduce cravings and withdrawal symptoms, and ease the transition from cigarette smoking to complete abstinence. Although there is high‐certainty evidence that NRT is effective for achieving long‐term smoking abstinence, it is unclear whether different forms, doses, durations of treatment or timing of use impacts its effects. Objectives To determine the effectiveness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 226 publications
(15 reference statements)
0
1
1
Order By: Relevance
“…The trial used a single NRT product as a comparator. A combination of NRT products is more effective than single NRT, and a trial that compared ECs with combination NRT reported a lower effect size at 6 months (RR, 1.36; 95% CI, 1.15- 2.6.9) than found in the current study. The finding that EC had similar efficacy to varenicline corresponded with a previous finding showing varenicline as superior to NRT, with a difference in efficacy similar to that found between EC and NRT …”
Section: Discussioncontrasting
confidence: 84%
“…The trial used a single NRT product as a comparator. A combination of NRT products is more effective than single NRT, and a trial that compared ECs with combination NRT reported a lower effect size at 6 months (RR, 1.36; 95% CI, 1.15- 2.6.9) than found in the current study. The finding that EC had similar efficacy to varenicline corresponded with a previous finding showing varenicline as superior to NRT, with a difference in efficacy similar to that found between EC and NRT …”
Section: Discussioncontrasting
confidence: 84%
“…Nicotine replacement therapy (NRT) through gum, lozenges, patches, sprays and inhalers doubles long-term quit rates compared to placebo. The choice of NRT format can be tailored to individual needs and preferences (Theodoulou et al 2023a). Beyond nicotine delivery, the antidepressant bupropion and the nicotinic receptor partial agonist varenicline also improve cessation outcomes.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…E-cigarettes aim to provide users with inhaled nicotine and smoking-related sensory cues while eliminating toxic combustion products responsible for the majority of smoking-related disease risks. This has led to considerable interest in evaluating whether e-cigarettes may represent a reduced harm nicotine product that can effectively promote smoking cessation (Theodoulou et al 2023b).…”
Section: Smoking Cessationmentioning
confidence: 99%
“…In line with standard smoking cessation research practice, 65 86 87 intention-to-treat analysis will be used for assessing effectiveness. Participants with missing smoking outcome data, that is, those who drop out of the study or who are lost to follow-up, and participants whose abstinence cannot be biochemically verified, will be considered as continuing smokers or to have resumed smoking.…”
Section: Methods and Analysismentioning
confidence: 99%